Adaptation of Leaders and The Implications of Law Number 18 Of 2019 Concerning Islamic Boarding Schools in Lumajang Regency - Sholeh, Farhanudin; Fauzi, Imron; Syafii, Imam; Hatta, Hatta (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
This study aims to explore the adaptation of leaders and the implications of Law Number 18 of 2019 concerning Islamic Boarding Schools in Lumajang Regency. This study is a qualitative study with a case study approach. The informants in this study were two leaders of Islamic boarding schools in Miftahul Ulum and Syarifuddin who were collected through interviews, observations, and documentation. Data analysis used the stages of data condensation, presentation, and conclusion. The results of the study indicate that the adaptation of policies implemented by the leaders of Islamic Boarding Schools in Miftahul Ulum and Syarifuddin in efforts to develop institutions is illustrated when there is a program formation carried out through democratic student deliberations and the existence of a formal education system. The implications of the strategy of Islamic boarding school leaders, namely leaders open various types of business fields.